Mechanical Harvesting and Tree Health - Richard S. Buker; James P. Syvertsen; Jacqueline K. Burns; Fritz M. Roka; William M. Miller; Masoud Salyani; Galen K. Brown (EDIS)
A typical concern voiced over mechanical citrus harvesters is “Do they harm trees?” Observing mechanical citrus harvesters reveals they can remove leaves, branches, bark, and sometimes immature Valencia fruit. This publication was designed to inform decision makers on the impacts of tree injury on the health and longevity of citrus trees. This publication addresses only one of several components that could influence your decision to mechanically harvest citrus trees–effects of mechanical harvesting on tree health. There are benefits to mechanically harvesting a citrus grove. The authors of this publication recommend reviewing other IFAS publications on mechanical harvesting before making a decision about mechanical citrus harvesters. This document is HS961, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published July 2004.